Earth keeper : reflections on the American land - Momaday, N. Scott, 1934- (Harper, an imprint of HarperCollinsPublishers, 2020)
"In Earth Keeper: Reflections on an American Land, Momaday reflects on his native ground and its influence on his people. "When I think about my life and the lives of my ancestors, I am inevitably led to the conviction that I, and they, belong to the American land. This is a declaration of belonging. And it is an offering to the earth." he writes. Earth Keeper is a story of attachment, rooted in oral tradition. Momaday recalls stories of his childhood that have been passed down through generations, stories that reveal a profound and sacred connection to the American landscape and a reverence for the natural world. In this moving work, he offers an homage and a warning. Momaday reminds us that the Earth is a sacred place of wonder and beauty; a source of strength and healing that must be protected before it's too late. As he so eloquently yet simply reminds us, we must all be keepers of the Earth"--